Entomological Surveillance of Malaria Vectors in Saumlaki, Maluku Tenggara Barat Regency, Maluku Province (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
The research aims to determine the prevalence of malaria and Anopheles spp using bio-ecology surveillance in Alusi and Waturu community health centers in Maluku Tenggara Barat Regency. The study was conducted in March-April 2015 with cross sectional design. In this research, we performed mass blood survey on 489 participants in the Kilmasa village and 434 participants in Waturu village. We also performed entomology surveillances, i.e. larval density, catching Anopheles spp, temperature, humidity, and salinity. To confirm malaria vectors, we used enzyme linked immunoabsorbent assay (ELISA) techniques. The data analyzed descriptively. The results of the study showed proportion 0.20% malaria morbidity in Kilmasa village and 0.23% in Waturu village. Anopheles flavirostris and An. barbirostris group were likely to bite a human outside and inside the house and peaked at 11.00 pm-12.00 pm. The parous rate of An. flavirostris and An. barbirostris was 46% and 26%, respectively. Human blood index of An.flavirostris and An. barbirostris was 33.3% and by 70%, respectively. Anopheles flavirostri and An. barbirostris were malaria vectors with sporozoite rate 0.38% and 12.5%, respectively.